2019
DOI: 10.24844/em3102.08
|View full text |Cite
|
Sign up to set email alerts
|

Las tecnologías en el aula para la enseñanza del contraste de hipótesis

Abstract: Resumen. Las tecnologías han influido de forma significativa en todos los campos, y en mayor medida en los temas relacionados con la estadística (Galmacci, 2001). La mayoría de las investigaciones sobre contraste de hipótesis describen errores en la interpretación del nivel de significación y el p-valor (ej., Vallecillos, 1994), existiendo poca presencia de investigaciones de errores sobre el contraste de hipótesis mediante el uso de tecnologías. Esto incentiva la realización de investigaciones con recursos in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…We conceive, by hypothesis testing, the procedure that allows verifying an assertion regarding the value of a population parameter from data obtained in a sample. In addition, in recent years in statistical education, specialists have reported teaching and research experiences on statistical reasoning for inference; for example, studying levels of statistical reasoning on hypothesis tests with mathematics students (Inzunza & Jiménez, 2013) and the impact of learning environments with the use of technologies (Cañadas et al, 2012(Cañadas et al, , 2019. Other investigations refer to the incorrect use of statistical hypothesis tests, erroneous interpretations of the results, confusion between null and alternative hypotheses (Vallecillos, 1999), student confusion between statistical and research hypotheses (Chow, 1996), conflict in the logic of the process of Fisher's significance tests and Neyman-Pearson's hypothesis testing (Vallecillos, 1999), confusion between bilateral and unilateral tests, and the regions of acceptance and rejection (Vera, 2017), difficulties in understanding the…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…We conceive, by hypothesis testing, the procedure that allows verifying an assertion regarding the value of a population parameter from data obtained in a sample. In addition, in recent years in statistical education, specialists have reported teaching and research experiences on statistical reasoning for inference; for example, studying levels of statistical reasoning on hypothesis tests with mathematics students (Inzunza & Jiménez, 2013) and the impact of learning environments with the use of technologies (Cañadas et al, 2012(Cañadas et al, , 2019. Other investigations refer to the incorrect use of statistical hypothesis tests, erroneous interpretations of the results, confusion between null and alternative hypotheses (Vallecillos, 1999), student confusion between statistical and research hypotheses (Chow, 1996), conflict in the logic of the process of Fisher's significance tests and Neyman-Pearson's hypothesis testing (Vallecillos, 1999), confusion between bilateral and unilateral tests, and the regions of acceptance and rejection (Vera, 2017), difficulties in understanding the…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Teachers and engineers use various technological resources in the classroom, depending on the conditions of laboratory equipment and software licenses of the institution. Cañadas et al (2019) evaluated R and SPSS software in terms of utility, ease of use, ease of learning, and satisfaction with 168 first-year university students. They concluded that both are effective and present good results in the application of hypothesis tests in the comparison of means, although they emphasize that SPSS has shown better attitudes in various fields.…”
Section: Ei6 Do You Use Statistical Software In the Application Of Hy...mentioning
confidence: 99%
“…La tecnología, término empleado para designar al conjunto de artefactos [digitales] y sus procesos de instrumentalización (Artigue, 2000), se presenta como una herramienta útil en la Educación Matemática, según investigaciones realizadas por Cañadas et al (2019), Rojano (2014), Steegman et al (2016) y Trouche et al (2012), entre otros. Lo que ratifican asociaciones como la National Council of Teachers of Mathematics (NCTM, 2000) que las declaran esenciales para hacer y aprender matemáticas.…”
Section: Introductionunclassified